Валерий Чкалов: повесть / Александр Беляков ; [автор предисловия Г. Байдуков] - Беляков Александр Васильевич (ДОСААФ, 1987)
Экземпляры: ЦБ, ф3, ф4, ф19, ф20 (20241223) / Инвентарный номер: 16986 / Цена: 0.85 / Сис.шифр: Р2 / Авт.знак: Б 44 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6